Cannabinoids and the endocannabinoid system in the regulation of cytochrome P450 metabolic activity-a review - Fonseca, Carlos D.F.; Zendulka, Ondřej; Juřica, Jan (Frontiers in Pharmacology, 2025)
The use of cannabinoids has a history spanning thousands of years, and their pharmacological and toxicological properties, particularly those of THC and CBD, are well-documented. However, their potential to induce drug-drug interactions remains underexplored. This review aims to provide a comprehensive perspective by contextualizing the historical and pharmacological significance of cannabinoids while focusing on their capacity to modulate the metabolic activity of cytochrome P450 isoforms relevant to drug metabolism. Additionally, we look at the impact of cannabinoids in neuronal circuits impacting the hypothalamic-pituitary hormonal axis, such as the locus coeruleus and raphe nuclei and their possible consequences on the cytochrome P450 system. Recognising potential interactions between cannabinoids and other drugs could enhance understanding of their pharmacological effects, improve the efficacy and safety profiles of cannabinoid-based therapies, and encourage further exploration into this under-researched area of psychopharmacology, with implications for both preclinical research and clinical practice.